Management of Post-Mastoidectomy Retroauricular Wound Dehiscence Using Advancement Flap: Case Report - Dewi Pratiwi; Desnita Monica (CV. Publikasi Indonesia, 2026)
Mastoidectomy with tympanoplasty commonly requires a postauricular incision and may be complicated by retroauricular wound dehiscence, particularly in the presence of infection, tissue tension, or impaired local perfusion. Persistent wound dehiscence can delay healing, compromise cosmetic outcomes, and necessitate secondary reconstructive procedures. Local advancement flaps and skin grafting are among the reconstructive options described. The purpose to report the clinical outcome of post-mastoidectomy retroauricular wound dehiscence managed using an advancement flap and review supporting evidence for this technique. Case report: A 52-year-old man with chronic suppurative otitis media with cholesteatoma underwent canal wall up mastoidectomy with tympanoplasty. During postoperative follow-up, retroauricular wound dehiscence complicated by local infection was identified. Surgical reconstruction was performed using a retroauricular advancement flap under general anesthesia. Postoperative follow-up demonstrated satisfactory wound closure, progressive epithelialization, and acceptable cosmetic outcomes, with no recurrence or major complications. Clinical question: Does advancement flap reconstruction offer better outcomes compared to skin grafting in post-mastoidectomy retroauricular wound dehiscence? Method: A literature search was conducted in PubMed, ScienceDirect, and Google Scholar to identify relevant studies on the management of post-mastoidectomy retroauricular wound dehiscence using advancement flaps or skin grafts. Seven relevant articles were identified. Case reports and small case series demonstrated high primary wound closure rates and low recurrence following advancement flap reconstruction. Skin grafting facilitated epithelialization in selected cases but showed variable outcomes in compromised wound beds. Advancement flap reconstruction is an effective and reliable option for managing retroauricular wound dehiscence following mastoidectomy, particularly in chronic or infected wounds.